KOMITMEN ORGANISASI MENERAPKAN NEW NORMAL MEMPERHATIKAN KEPEMIMPINAN TRANSFORMASIONAL DIMEDIASI KESIAPAN UNTUK BERUBAH - Mokhammad Khukaim Barkhowa; Taufiq Andre Setiyono; Achmad Danang Setiawan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The Policy for the Implementation of Restrictions on Community Activities at the Salatiga City level greatly affects the company's activities in Salatiga City. In this case, it is necessary to have transformational leaders and employee readiness to make changes so that the organization commits to adapt to the current new normal era. The purpose of this study is to examine how transformational leadership affects organizational commitment with readiness to change as mediation for company employees in Salatiga City. Sampling in this research uses the calculation with the Slovin formula with a sample of 100 employees. Sampling using snowball sampling. There are 3 measuring tools for data analysis in testing the hypothesis: Simple Regression Analysis, Multiple Regression Analysis, and Sobel Test through Classical Assumption Test and Model Goodness Test. The resulting analysis model is declared good. The results of hypothesis testing are transformational leadership has a positive effect on readiness to change, readiness to change has a positive effect on organizational commitment, and transformational leadership affects organizational commitment through readiness to change.